Mitochondrial uncouplers inhibit clathrin-mediated endocytosis largely through cytoplasmic acidification - Dejonghe, Wim; Kuenen, Sabine; Mylle, Evelien; Vasileva, Mina; Keech, Olivier; Viotti, Corrado; Swerts, Jef; Fendrych, Matyáš; Ortiz-Morea, Fausto Andres; Mishev, Kiril; Delang, Simon; Scholl, Stefan; et al. (Nature Communications, 2016)
Plant cells maintain strict proton gradients over different membranes. Here, Dejonghe et al. show that several protonophores, including the known tyrosine kinase inhibitor TyrphostinA23, inhibit clathrin-mediated endocytosis by disturbing these gradients and causing cytoplasmic acidification.
Gesehen am 07.05.2020